Membranoproliferative glomerulonephritis with syphilis involvement and possible Hepatitis B virus contribution: a case report - Yan Pan; Jiqiang Zhang; Lei Liu; Ruiping Zhao; Tiekun Li; Weidong Chen (BMC Nephrology)
Abstract Background Syphilis, a sexually transmitted disease, presents with a wide range of clinical manifestations. As the global rate of syphilis infection continues to rise, so does the incidence of syphilis-associated nephritis. Characterized by diverse clinical and pathological features, the disease shows a good response to penicillin treatment. This article presents the case of a 46-year-old Chinese male patient exhibiting edema, hematuria, proteinuria, and a tendency towards rapidly progressive glomerulonephritis (RPGN). The patient was diagnosed with membranoproliferative glomerulonephritis (MPGN), with syphilis being a likely etiology and co-infection with Hepatitis B virus (HBV). He was treated with benzathine penicillin for three weeks, followed by low-dose glucocorticoids and mycophenolate mofetil (MMF) for subsequent treatment, leading to a significant improvement in his condition. Conclusion Highlighting the significance of syphilis as a cause of nephritis and emphasizing the importance of timely diagnosis and treatment can greatly alleviate the patient’s condition. Additionally, the role of Hepatitis B virus as a contributing factor in the development of nephritis should not be overlooked. Clinical trial number Not applicable.